JUST-IN-TIME ASSESSMENT IN FOREIGN LANGUAGE ACQUISITION - Pardayevna, Kurbanova Niginabonu (FAN, TA’LIM VA AMALIYOT INTEGRATSIYASI, 2022)
One of the most important aspects of language teaching and learning is assessment. Language learning assessment serves one of two purposes: either it measures learners’ proficiency without reference to a language course or it measures the extent to which they have achieved the goals of a specific learning program. Teachers typically use assessments to monitor students’ first or second language development as well as the quality of their day-to-day subject matter learning. Formative assessment provides teachers with a better understanding of their students’ language and content understanding than standardized summative assessments, which typically do not account for an English language learner’s (ELL) language proficiency level or the quality of his or her content. Unlike the types of assessment described above, there is one more grading type in the process of language acquisition. In the current article, the Just in time assessment and its functions, its importance, and its notion will be analyzed.